Safe Drilling Paths in the Distal Femoral Epiphysis for Pediatric Medial Patellofemoral Ligament Reconstruction. (April 2017) - Nguyen, Cynthia V.; Farrow, Lutul D.; Liu, Raymond W.; Gilmore, Allison
Background: Anatomic surgical reconstruction of the medial patellofemoral ligament (MPFL) has been popularized for the treatment of recurrent patellar instability in the skeletally immature population. Previous anatomic studies have found that the femoral attachment point of the MPFL is very close to the distal femoral physis. Purpose: To establish the safe angles for drilling the distal femoral epiphysis for MPFL graft placement. Study Design: Descriptive laboratory study. Methods: A total of 23 cadaveric distal femoral epiphyses were scanned into high-resolution 3-dimensional images. Using computer-aided design, we identified and marked the femoral insertion site of the MPFL. Cylinders 8 mm in diameter were placed at varying angles to simulate the drill paths for placement of 6-mm interference screws with a 1-mm buffer. The distance from the MPFL footprint to where the tunnel first violated the physis, the intercondylar notch, or the distal cartilage was measured. We recorded the percentage of tunnels that caused violations before reaching 20 mm, the shortest length of a typical femoral tunnel socket. Results: Measurements indicated that 41% of tunnels angled distally less than 10° violated the physis, 40% of tunnels angled distally more than 10° but anteriorly less than 10° violated the notch, and 27% of tunnels angled distally and anteriorly more than 20° violated the distal femoral cartilage. At least 90% of the tunnels were safe at 20 mm when the drill was angled between 15° and 20° both anteriorly and distally. Conclusion: Because of the anatomy of the distal femoral physis, drilling into the epiphysis from the MPFL attachment site at improper trajectories risks damage to sensitive structures. Angling the drill to an acceptable degree distally and anteriorly leads to less risk to the physis and notch, respectively, but angling too much leads to risk to the distal femoral cartilage. Small variations in the sagittal plane were better tolerated than variations in the coronal plane, so we recommend that more attention be paid to the radiographic anteroposterior view intraoperatively. It is safest to angle the drill distally and anteriorly approximately 15° to 20° in each plane from the MPFL attachment site. Clinical Relevance: During drilling into the distal femoral epiphysis at the MPFL origin in skeletally immature patients, angling the drill appropriately 15° to 20° both distally and anteriorly minimizes damage to the physis, notch, and distal femoral cartilage.